Pendampingan Industri Rumah Tangga Kuliner Roti di Desa Mangga Dua Kecamatan Tanjung Beringin Kabupaten Serdang Bedagai - Deo Demonta Panggabean; Izwar Lubis; Ali Fikri Hasibuan; Mukti Hamjah Harahap; Irfandi Irfandi; Dedy Husrizal Syah (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
The purpose of this PKM activity is to carry out the Tri Dharma of Higher Education especially in the field of Community Service to assist partners in solving the problems they face, starting from the aspect of production and business management so that it is expected to create economic independence and increase business income. In the aspect of production, partners experience constraints on the effectiveness of production time due to the minimal capacity of the toaster oven. While in the aspect of business management in terms of bookkeeping management partners have not been able to record financial transactions properly so that partners find it difficult to be able to apply for financial assistance as additional business capital. The method used in the implementation of this community service is the method of approach in the form of training, practice, and assistance. The results obtained from the implementation of community service activities are 1). Partners can do financial records properly, 2). The availability of appropriate technology stainless gas-fired ovens with a capacity of 14 racks, 4) Shorter baking time for the baking dough, 5). There are 5 types of bread product packaging labels, 6). Partners have a business license, halal product certificate, and UMKM registration certificate.